When Green Tax Fails: How Tax Avoidance Undermines Sustainable Performance in Indonesia - Natsir, Andi Iqra Pradipta; Kusumawati, Andi; Furqan, Muhammad; Djakiman, Cilun (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
Set within Indonesia’s UU HPP carbon-pricing regime, this study tests whether green tax pressure, access to green finance, and green employee behaviour improve sustainable firm performance through corporate social responsibility (CSR), and whether tax avoidance weakens this pathway. Evidence comes from a cross-sectional survey of 230 finance, CSR, and HR managers in energy, banking, and transportation firms, analysed with prediction-oriented PLS-SEM (SmartPLS 4) using mediation and moderation. Green tax, green finance, and green employee behaviour each relate positively to CSR; CSR, in turn, associates with higher sustainability performance on economic, social, and environmental dimensions. Tax avoidance significantly reduces the strength of the green tax–CSR association (interaction β = −0.19), indicating that aggressive fiscal conduct can blunt the intended behavioural effects of carbon-pricing signals. Measurement and structural diagnostics meet contemporary thresholds and indicate meaningful explanatory and predictive power. Implications include aligning carbon-tax incentives with risk-based anti-avoidance oversight and tax-transparency disclosure, embedding auditable CSR metrics in green instruments, and institutionalising pro-environmental routines while integrating tax, finance, and sustainability governance. The cross-sectional, sector-bounded design motivates longitudinal, multi-source extensions as Indonesia’s carbon pricing matures.